2020
DOI: 10.1097/hn9.0000000000000025
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic considerations for functional endoscopic sinus surgery: a narrative review

Abstract: This review article discusses state-of-the-art perioperative anesthesia care for patients presenting for functional endoscopic sinus surgery (FESS). A comprehensive literature review (years 2000–2019) was performed with a focus on FESS topics related to preoperative patient evaluation and preparation, airway management, and optimization of the major anesthetic and surgical goals. The authors identify and elaborate in detail on essential intraoperative considerations, such as the use of controlled hypotension a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 156 publications
0
5
0
Order By: Relevance
“…Effective hemostasis is crucial during FESS since even minor bleeding can severely compromise an already restricted view in the narrow nasal space, prolong the operation, and increase the risk of damage to sensitive tissue structures. The lowering of MAP during general anesthesia can minimize intraoperative bleeding, reduce the time of operation, and improve the quality of surgery ( 3 , 10 ). A prospective, observational cohort study showed that MAP below 60 mmHg was associated with better surgical visibility in terms of bleeding assessment score ( 1 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective hemostasis is crucial during FESS since even minor bleeding can severely compromise an already restricted view in the narrow nasal space, prolong the operation, and increase the risk of damage to sensitive tissue structures. The lowering of MAP during general anesthesia can minimize intraoperative bleeding, reduce the time of operation, and improve the quality of surgery ( 3 , 10 ). A prospective, observational cohort study showed that MAP below 60 mmHg was associated with better surgical visibility in terms of bleeding assessment score ( 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…After the surgery, the surgical field was evaluated by the surgeon using Fromme score, which is as follows: 1-slight bleeding without the requirement for blood suctioning, 2-slight bleeding requiring occasional suctioning but surgical field not compromised, 3-slight bleeding requiring frequent suctioning and surgical field affected within a few seconds of removing suction, 4-moderate bleeding requiring frequent suctioning and surgical field directly compromised by bleeding after suction is removed, and 5-severe bleeding that overwhelmed constant suctioning and severely compromised the surgical field and prevented surgery (9).…”
Section: Experimental Protocolsmentioning
confidence: 99%
“…ESS aims to create a clear surgical field during the procedure by minimizing bleeding and avoiding injuries to the vascular, cerebrospinal fluid, and orbital tissues [1,[6][7][8]. To achieve this, various techniques are used to reduce blood flow to the intraoperative field.…”
Section: Role Of Anesthesia In the Intraoperative Fieldmentioning
confidence: 99%
“…It is essential for ESS to achieve optimal intraoperative surgical field visibility and minimize blood loss, which is one of the critical factors for successful outcomes. Factors that can influence bleeding during ESS include the use of antiplatelet and/or anticoagulant drugs, hypertension, the Lund-Mackay CT score, damage to vessels due to the altered anatomy, lack of surgeon experience, extensive sinus disease, revision surgery, and poor visualization [1][2][3][4][5]. Intraoperative bleeding during ESS can be challenging due to the narrow sinonasal surgical field, single working hand, and the use of endoscopic instruments, which may affect hemostasis [3].…”
Section: Introductionmentioning
confidence: 99%
“…The essential anesthesia requirements for FESS include airway management, considerations for facilitating surgical access, provision of a clear and still surgical field for precision surgery, assuring quick and non-stimulating emergence from anesthesia, and fast-tracking patients for discharge [2].…”
Section: Introductionmentioning
confidence: 99%